2017
DOI: 10.1002/ejlt.201700108
|View full text |Cite
|
Sign up to set email alerts
|

Phenolics, fatty acids, and biological potential of selected Croatian EVOOs

Abstract: Nutritional value of extra virgin olive oil is associated with its complex chemical composition. The aim of this study was to determine phenolic secoiridoids in Extra virgin olive oils (EVOOs) from autochthonous Croatian cultivars (Drobnica, Krvavica, Lastovka, and Oblica) by qNMR, to determine simple phenolics by UPLC, as well as to analyze the fatty acid profile, the antioxidant activity, and the oxidative stability of selected oils. This is the first study on chemical and biological characterization of sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The determined concentrations of hydroxytyrosol in VOO and VOO-Sea, that amount to 18.2 mg/kg and 12.9 mg/kg, respectively, are generally in the range similar to the values in some Spanish (6.9–72.7 mg/kg of oil) or Italian EVOOs (0.85–36.7 mg/kg of oil) [ 17 , 19 , 20 ], and are even higher than those previously published for Oblica variety (6.2–11.3 mg/kg of oil) [ 11 , 21 , 22 ]. Furthermore, the tyrosol concentration determined in VOO and VOO-Sea (8.10 mg/kg and 7.20 mg/kg respectively) is very similar to the values in the same literature.…”
Section: Resultssupporting
confidence: 82%
“…The determined concentrations of hydroxytyrosol in VOO and VOO-Sea, that amount to 18.2 mg/kg and 12.9 mg/kg, respectively, are generally in the range similar to the values in some Spanish (6.9–72.7 mg/kg of oil) or Italian EVOOs (0.85–36.7 mg/kg of oil) [ 17 , 19 , 20 ], and are even higher than those previously published for Oblica variety (6.2–11.3 mg/kg of oil) [ 11 , 21 , 22 ]. Furthermore, the tyrosol concentration determined in VOO and VOO-Sea (8.10 mg/kg and 7.20 mg/kg respectively) is very similar to the values in the same literature.…”
Section: Resultssupporting
confidence: 82%
“…We found that olive oil from Buza has a significantly higher level of oleic acid than Drobnica, which corresponds with results from the multi-year data ranging from 1992 to 2009 in Istria where the level of oleic acid in the Buza variety was 74% [ 20 ] or near 74% [ 11 ]. In Drobnica, cultivated in Dalmatia, oleic acid was found to be lower (near or under 70%) [ 7 , 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…This also affected the highest antioxidant activity of Drobnica oil and it’s very long (23 h) oxidative stability as determined by the Rancimat method. Similarly, Dalmatian monovarietal olive oils were analysed in relation to the harvest period (Buhavica, Drobnica, Lastovka and Oblica) [ 8 ]. It was observed that the late harvest contained an extremely high concentration of oleocanthal + oleacein (966 mg/kg) in EVOO from Drobnica, and that oils from Drobnica and Lastovka (Korčula Island, South Dalmatia, position 42°57′31.62′′ N) had the longest oxidative stability (20.95 and 18.65 h, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations